Pentingnya Pencatatan Keuangan yang Akurat untuk Keberhasilan UMKM Kedai Mochi Gaol - Marlinda Ina; Viery Erlangga Nugraha; Revalina Dwi Anggita; Aura Shavina Unnov Salsabilla; Dewa Wahyu Aryanta; Sri Rahayuningsih (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
UMKM Mochi Gaol is a business engaged in the production and sale of mochi. This report aims to provide an overview of the performance of Mochi Gaol UMKM over a period of 1 month. This research was conducted by qualitative descriptive method. Data was collected through interviews with UMKM owner Mochi Gaol, direct observation at the place of business, and analysis of related documents. UMKM Mochi Gaol was founded in 2020 by Putri Retno Mengasih. This business produces various types of mochi with unique flavors and variations. UMKM Mochi Gaol markets its products through online and offline. During the 1-month period, Mochi Gaol UMKM experienced an increase in sales. This is driven by several factors, such as the increasing popularity of mochi, effective marketing strategies, and good product quality. Mochi Gaol UMKM also face several challenges, such as intense competition, limited capital, and limited access to raw materials. To overcome this challenge, Mochi Gaol UMKM need to improve the quality of their products, expand their marketing strategies, and establish cooperation with other parties. The conclusion from the results of the Mochi Gaol UMKM research shows that the Mochi Gaol business has bright prospects. With the right strategy, Mochi Gaol UMKM can continue to develop and contribute to the local economy.